The Vascularized Medial Femoral Corticoperiosteal Flap for Thumb Reconstruction. Issue 8 (August 2015) - Ruston, Julia C.; Amin, Kavit; Darhouse, Nagham; Sivakumar, Bran; Floyd, David
Abstract : Summary: We present an interesting method of shaping a vascularized medial femoral condyle (MFC) flap into a "neophalanx" for phalangeal reconstruction. Our patient presented with limited strength and function secondary to fracture nonunion of the proximal phalanx of the dominant thumb. Following excision of the pseudarthrosis, an MFC corticoperiosteal flap was harvested, sculpted into a prism shape and inset. The superomedial genicular pedicle was anastomosed to the princeps pollicis artery and a cephalic tributary. On follow-up, new bone growth was seen on radiographs and the patient had substantially improved function, with full metacarpophalangeal extension, a Kapandji score of 9, and a markedly reduced Disabilities of the Arm, Shoulder and Hand score of 2.68. The MFC flap is useful for reconstruction of bony defects, with minimal donor morbidity. This versatile vascularized flap can be crafted to requisite shapes and is useful for small defects in the hand, including phalangeal reconstruction. Abstract : Supplemental Digital Content is available in the text.